1993
DOI: 10.1051/lait:1993218
|View full text |Cite
|
Sign up to set email alerts
|

Amélioration de la résistance des lactocoques aux bactériophages

Abstract: Résumé -Les phages sont reconnus depuis longtemps comme la principale cause de ralentissement de la croissance des lactocoques composant les levains de fromagerie. La sélection de souches naturelles ou mutantes particulièrement résistantes aux phages ne permettant pas un contrôle optimum des fabrications, une nouvelle approche a été envisagée après analyse des méca-nismes de résistance aux phages naturellement présents dans les souches. Il s'agit de construire des souches plus résistantes aux phages par accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1993
1993
1997
1997

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Chopin and co-workers have reported the cloning of three Abi determinants from lactococ- 100 cal DNA [100,101]. The first of these abortive infection genes has been cloned on a 2-kb fragment from total DNA isolated from L. lactis subsp, lactis IL416 [100].…”
Section: Abi416 Abil05 and Abi420mentioning
confidence: 99%
See 1 more Smart Citation
“…Chopin and co-workers have reported the cloning of three Abi determinants from lactococ- 100 cal DNA [100,101]. The first of these abortive infection genes has been cloned on a 2-kb fragment from total DNA isolated from L. lactis subsp, lactis IL416 [100].…”
Section: Abi416 Abil05 and Abi420mentioning
confidence: 99%
“…The same laboratory has also reported that the sequence of a second Abi gene has been determined [101]. This gene, designated abil05, was cloned from the lactococcal plasmid piLl05.…”
Section: Abi416 Abil05 and Abi420mentioning
confidence: 99%